(untitled) (International Journal of Engineering and Computer Science, 2017)
The paper presents an researchon the development of RF based type of antenna. The genetic algorithm is used to optimize the two antenna architecture.The ground plane is taken as dimension 100.5×100.5×1.5. .On the other hand metal plate have dimension 16.71×1.5×110.52 mm. The main goal of the article is a comparison of directivity and bandwidth of the proposed antennas. In our analysis, the method of moments (MoM) is used to compute the currentdistribution and directivity of the yagi antenna. Microstrip technology is used for planar collinearmonopole antenna and simulation with ground plane has been performed using Ansoft HFSS 3Dsimulator. Prototypes have been realized and measured.